Propofol versus traditional sedative agents for advanced endoscopic procedures: A meta‐analysis. Issue 4 (19th December 2013) - Sethi, Saurabh; Wadhwa, Vaibhav; Thaker, Adarsh; Chuttani, Ram; Pleskow, Douglas K.; Barnett, Sheila R.; Leffler, Daniel A.; Berzin, Tyler M.; Sethi, Nidhi; Sawhney, Mandeep S.
<x xml:space="preserve">Abstract</x> Background and Aim The optimum method for sedation for advanced endoscopic procedures is not known. Propofol deep sedation has a faster recovery time than traditional sedative agents, but may be associated with increased complication rates. The aim of the present study was to pool data from all available studies to systematically compare the efficacy and safety of propofol with traditional sedative agents for advanced endoscopic procedures. Methods Databases including PubMed, Embase, Web of Science and the Cochrane Central Register of Controlled Trials updated as of January 2013 were searched. Main outcome measures were procedure duration, recovery time, incidence of complications (hypotension, hypoxia), sedation level, patient cooperation and amnesia during advanced endoscopic procedures such as endoscopic retrograde cholangiopancreatography, endoscopic ultrasonography, and deep small bowel enteroscopy. Results Nine prospective randomized trials with a total of 969 patients (485 propofol, 484 conscious sedation) were included inthe meta‐analysis. Pooled mean difference in procedure duration between propofol and traditional sedative agents was −2.3 min [95% CI: −6.36 to 1.76, P = 0.27], showing no significant difference in procedure duration between the two groups. Pooled mean difference in recovery time was −30.26 min [95% CI: −46.72 to −13.80, P < 0.01], showing significantly decreased recovery time with propofol. There was also no significant difference between the two groups with regard to hypoxia and hypotension. Conclusions Propofol for advanced endoscopic procedures is associated with shorter recovery time, better sedation and amnesia level without an increased risk of cardiopulmonary complications. Overall patient cooperation was also improved with propofol sedation.